Facebook Posts : Exploration and Comprehension of Sensationalism - Trivedi, Shekhar; Dikshit, Shashi Kant (Prabandhan: Indian Journal of Management, 2020)
The research was done to explore and ratify sensationalism in Facebook posts as is present in the mass media. The question is whether the news through Facebook posts evokes sensationalism in the same way as it happens in case of mass media. To check the degree of sensationalism, 150 posts from three genres of crime, politics, and social interest were chosen as a stimulus in the form of news. Fifty respondents responded to 150 posts on a 7 - point Likert scale. The research tried to understand whether there is any difference in sensationalism towards sensational Facebook posts among people, or is it the same ; is there any difference in sensationalism towards Facebook posts from three different areas of crime, politics, and social interest; and whether people responded differently to foreign crime and Indian crime posts. The study also examined whether pro - BJP and anti - BJP posts evoked a different level of sensationalism. The research concluded that people exhibited a different degree of sensation towards sensational posts on Facebook ; while crime posts were found to be more sensational than social interest posts and political posts, the crime posts from the US scored higher than the Indian crime posts on being sensational.